Health Impacts of Indiscriminate Dumping of Solid Waste Disposal in Wukari Local Government Area, Taraba State, Nigeria - Peter Ujulu; Ugwu Immaculata Chidebere (African Journal of Sciences and Traditional Medicine, 2026)
This study examines the health impacts of indiscriminate dumping of solid waste disposal in Wukari Local Government area Taraba State, Nigeria. It aimed at identifying composition of waste material, assessed waste management practice among the residents, assessed health implications of indiscriminate dumping of solid waste disposal in the study area. Primary data was obtained through a set of questionnaire to the waste generators. A structured questionnaire was distributed randomly in residential areas, market/public places, schools, workshops and business centres within the study area. The sample size of this study consisted of 400 respondents household head in Wukari was sampled for the study. The data collection was sequentially using field observation and questionnaires. The data obtained was analysed using SPSS (statistical package for social sciences) version 25.0 to determine frequency distribution, percentage ratio and mean. The result was presented in tables for better understanding. The finding showed different types of waste generated in the study area as polythene waste constituted 33.4%. Clothe/carton/paper wastes constituted 27.3%. Crop residue/food remains 18.0%. Plastics waste, 15.9% while can/tins/battles waste constituted 5.4% of the total waste generated. Survey revealed that about 43.1% of the household heads which constituted a majority dumped their wastes in open space. Based on the result, it was observed that educational level had positive impacts on the waste management practices.